Enhanced Optimal CDT with Appropriate Contention Count based on CNM in MANET - Sivapriya, N; Ravi, T.N; Mohandas, R (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad hoc Networks (MANETs) are a class of infrastructure less networks that are created through a number of autonomous wireless and mobile nodes. The inherent characteristics of such networks create the support of multimedia applications very challenging. In previous researches, the capacity and delay in MANETs was analyzed via considering the correlation of node mobility. Explored the characteristics of correlated mobility and figured out the essential relationships among the scheduling parameters and the network performance. However, the reliability and link stability for transmitting the packets is needed in MANET to achieve Quality of Service (QoS) support in terms of available bandwidth, high throughput and stable jitter. Hence, QoS aware metric for routing is incorporated with the Correlated Mobility (CM). In this method, Link Stability Factor(LSF) is estimated by considering received signal strength, the appropriate contention count and hop count. On the basis of the estimated LSF, stable link is determined. After that, the node with the highest LSF is elected as a reliable forwarding node. So, the proposed method improves QoS performance. The simulation results proved that our proposed methods are providing better results.